Business process reengineering as a factor of integrated economic resilience growth in developer structures throughout the enterprise life cycle - Fesun , A. (Ways to Improve Construction Efficiency, 2022)
The article presents a methodology for evaluating business process reengineering (BPR) projects in construction developer structures, taking into account the phases of their life cycle, industry specifics, and multilevel stakeholder interaction. A conceptual and analytical approach to the attribution of reengineering projects is proposed, based on four key criteria: the level of transformation complexity, functional coverage, impact on cost-time parameters, and long-term efficiency potential. It is substantiated that under current conditions of high environmental dynamics and economic digitalization, BPR is no longer merely an optimization tool but is transforming into a comprehensive concept of strategic renewal aimed at achieving integrated enterprise resilience. The proposed matrix model provides a structured assessment of the alignment of reengineering initiatives with key management parameters: complexity, scope, time-cost impact, and expected effectiveness. The research results confirm that effective attribution of BPR projects enables the identification of the most relevant areas of intervention in the developer’s organizational structure, the justified ranking of transformational initiatives, and improved decision-making quality. It is demonstrated that BPR implementation should be differentiated according to the enterprise life cycle phase – from project initiation to modernization or decommissioning. Special attention is given to the role of digital technologies (including BIM, ERP, and digital twin systems) as catalysts for reengineering that enhance the flexibility and adaptability of business processes. The generalization of Ukrainian scholars’ contributions has expanded the analytical framework of the study and supported the development of comprehensive, digitally oriented models for managing resilient developer structures in the construction industry.